Oral breathing: dentomaxillofacial irregularities associated with nasorespiratory and orthopedic dysfunctions. - Clotilde de la Caridad Mora Pérez; Salamtu Habadi Amhed; Juan J. Apolinaire Pennini; Raúl López Fernández; Ivette Álvarez Mora; Humberto Agüero García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Human beings are conditioned to breathe through the nose and feed through the mouth, when this physiological mechanism is interrupted facial and general growth is also affected. Objective: To characterize Angle´s Class II malocclusions in oral breathers with nasorespiratory and orthopedic dysfunctions. Method: A correlational, observational and descriptive study was developed from December 2004 to November 2005 including clinical examination of 833 children out of which 60 were selected to take part in this study. Each case was analyzed in Orthodontia, Orthopedics and Otolaryngology consultations. The studied variables were: age, sex, nasorespiratory disorders, orthopedic dysfunctions, dental-maxillofacial irregularities. Results: The mot frequent dental-maxillofacial irregularities were: bilabial incompetence, transversal micrognathism, vestibular version, overjet and overbite. The most important nasorespiratory dysfunctions found in these children were adenoiditis, and tonsil hypertrophy. The most outstanding orthopedic dysfunction was ciphosis. Conclusion: It is conclusive to state that there is a high relationship between dentomaxillofacial anomalies and nasorespiratory and orthopedic dysfunctions.